2022
DOI: 10.1021/acs.joc.2c00386
|View full text |Cite
|
Sign up to set email alerts
|

An Isoxazole Strategy for Molybdenum-Mediated Synthesis of 5-Mono- and 4,5-Disubstituted 1H-Pyrrole-2,3-diones

Abstract: The synthesis of 5-aryl-and 4-aryl/hetaryl/cyclopropyl/ alkynyl-5-aryl-1H-pyrrole-2,3-diones by formal isomerization of isoxazole-5-carbaldehydes mediated Mo(CO) 6 in wet MeCN has been developed. The resulting 1H-pyrrole-2,3-diones are good precursors for substituted 1H-pyrrolo[2,3-b]quinoxalines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Until now, the only known diazo compounds with an azirine substituent were 2-(diazoacetyl)­azirines 1 synthesized by the reaction of 2 H -azirine-2-carbonylchlorides 2 with N -isocyanotriphenyliminophosphorane or diazomethane. , To try to implement Strategy 3, we reacted 2-(diazoacetyl)­azirine 1a (R 1 = Ph) with a Rh­(II) catalyst [Rh 2 (OAc) 4 , Rh 2 (esp) 2 , Rh 2 (piv) 2 , and Rh 2 (oct) 4 ] in refluxing DCE but obtained a very complex mixture of non-isolable products. This may be due to the fact that primary product 3 , the nonfunctionalized derivative of still illusory 3 H -pyrrol-3-one, can easily undergo oligomerization as well as can nonselectively react with the rhodium carbene derived from 1 (Scheme ). In an attempt to either stabilize pyrrole 3 by reaction with water affording hydroxy compound 4 or at least to obtain the product of rhodium carbene insertion into the water O–H bond, compound 5 , reaction of (diazoacetyl)­azirine 1a was carried out in a THF/water mixture in the presence of a Rh 2 (OAc) 4 catalyst (Scheme ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Until now, the only known diazo compounds with an azirine substituent were 2-(diazoacetyl)­azirines 1 synthesized by the reaction of 2 H -azirine-2-carbonylchlorides 2 with N -isocyanotriphenyliminophosphorane or diazomethane. , To try to implement Strategy 3, we reacted 2-(diazoacetyl)­azirine 1a (R 1 = Ph) with a Rh­(II) catalyst [Rh 2 (OAc) 4 , Rh 2 (esp) 2 , Rh 2 (piv) 2 , and Rh 2 (oct) 4 ] in refluxing DCE but obtained a very complex mixture of non-isolable products. This may be due to the fact that primary product 3 , the nonfunctionalized derivative of still illusory 3 H -pyrrol-3-one, can easily undergo oligomerization as well as can nonselectively react with the rhodium carbene derived from 1 (Scheme ). In an attempt to either stabilize pyrrole 3 by reaction with water affording hydroxy compound 4 or at least to obtain the product of rhodium carbene insertion into the water O–H bond, compound 5 , reaction of (diazoacetyl)­azirine 1a was carried out in a THF/water mixture in the presence of a Rh 2 (OAc) 4 catalyst (Scheme ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…We began our study on the rearrangement of oxadiazoles 1 to pyrimidines 3 by synthesizing oxadiazole 1a according to a published procedure. 19 For the cleavage of the N-O bond in isoxazoles, various catalytic hydrogenation systems were used: H 2 /Ni, 21,22 H 2 /Pd, 23 H 2 /Pt, 24 H 2 O/Mo(CO) 6 [17][18][19][20][25][26][27] and H 2 O/ hν/Fe(CO) 5 . 26,28 Test experiments showed that hydrogenation on nickel, palladium or platinum catalysts provided complex mixtures of products, while the use of H 2 O/Mo(CO) 6 and H 2 O/ hν/Fe(CO) 5 led to the formation of the target product pyrimidine 3a.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, only a few examples of the use of C-C(CO 2 R)-C-N-C(Ar)-N blocks, which allow for obtaining pyrimidine-5-carboxylates with an aryl substituent at position 2 are known (Scheme 1, eqn (3)). 15,16 Based on our experience on the use of the hydrogenative cleavage of the N-O weak bond in isoxazoles to obtain pyrrole 17,18 and pyridine 19,20 derivatives, we hypothesized that the hydrogenative cleavage of the N-O bond in oxadiazoles 1 would result in the C-C(CO 2 R)-C-N-C-N building block 2 which is suitable for further cyclization into 6-oxo-1,6-dihydropyrimidine-5-carboxylates 3 (Scheme 1, eqn (4)). In this work, we report an effective one-pot method for the preparation of diverse 2-aryl-4-alkyl/aryl-6-oxo-1,6-dihydropyrimidine-5-carboxylates 3 via a metal carbonyl-promoted rearrangement of 2-(3-aryl-1,2,4-oxadiazol-5-yl)-3-oxopropanoates 1.…”
Section: Introductionmentioning
confidence: 99%